C-Four’s Efforts to Boost the Life Spirit of Cancer Patients in a Shelter Home - Mangolifi, Bonio; Fauziah, Mira; Duri, Rofiqa (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to analyze the role and efforts of the C-Four community in improving the morale of cancer patients. Cancer patients often experience psychological distress, such as hopelessness, anxiety, and decreased motivation due to their illness and the lengthy treatment process. In this context, social and emotional support from the community is a crucial factor in helping patients maintain their morale. This study used a qualitative approach, collecting data through in-depth interviews, observation, and documentation. Research informants were selected using a purposive sampling technique involving C-Four community administrators and cancer patients involved in the community's activities. Data analysis was conducted inductively through data reduction, data presentation, and conclusion drawing, with triangulation used to enhance data validity. The results show that the C-Four community plays a significant role in improving the morale of cancer patients through various activities, such as providing emotional support, psychosocial support, motivational activities, and experience-sharing programs among patients. The presence of this community provides a sense of togetherness, hope, and motivation for patients to continue their treatment with a more positive attitude. Furthermore, interactions between community members also help patients feel less alone in facing their illness. This study recommends that community support such as C-Four continue to be developed through collaboration with health workers, social institutions, and the government so that support programs for cancer patients can run more optimally and sustainably.